2017
DOI: 10.1130/ges01441.1
|View full text |Cite
|
Sign up to set email alerts
|

Decelerating uplift at Lazufre volcanic center, Central Andes, from A.D. 2010 to 2016, and implications for geodetic models

Abstract: Interferometric synthetic aperture radar (InSAR) and GPS measurements beyond 2010 are presented for the first time for the Lazufre volcanic center in the Central Andes. Vertical uplift at Lazufre was known to affect an area >50 km in diameter at rates exceeding 3 cm/yr between 1997 and 2010. Analy sis of new InSAR data through August 2016 indicates that the spatial pattern of uplift is relatively unchanged but the amplitude of uplift has significantly de creased to <1.5 cm/yr since at least December 2011. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…The mechanisms of posteruption deformation are complex and uplift could be the result of the repressurization of the magmatic system and/or viscous relaxation (Segall, 2016). Additional data sets such as repeated gravity surveys or continuous gas monitoring will be required to discriminate between the two processes (Henderson et al., 2017). We do not detect any deformation for the period 2015–2020 at two other centers having records of unrest (Table 1): Ayelu (dike intrusion) and Tendaho (geothermal).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of posteruption deformation are complex and uplift could be the result of the repressurization of the magmatic system and/or viscous relaxation (Segall, 2016). Additional data sets such as repeated gravity surveys or continuous gas monitoring will be required to discriminate between the two processes (Henderson et al., 2017). We do not detect any deformation for the period 2015–2020 at two other centers having records of unrest (Table 1): Ayelu (dike intrusion) and Tendaho (geothermal).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous geophysical studies over the past 20 yr indicate the presence of two shallow crustal inflation sources beneath Lastarria's edifice, presumed to represent magma and magmatic-hydrothermal fluids, respectively. Specifically, InSAR geophysical observations by Pearse and Lundgren (2013) found continued inflation of the ~8-km-depth deformation source beneath the Lazufre region between 2005 and 2010, and again by Henderson et al (2017) through 2016. To sustain this continuous inflation, we assume that magma has been continuously supplied to this ~8-km-depth crustal storage region from deeper within the crust through 2016.…”
Section: Integration With Geophysical Modelsmentioning
confidence: 98%
“…Ruch et al (2009) similarly observed a shallow inflation source at a depth of ~1 km between 2000 and 2008. Continued inflation of the 7-15 km source has been observed through 2010 at an average rate of 3 cm/yr by Pearse and Lundgren (2013) and at a reduced rate of <1.5 cm/yr between 2011 and 2016 by Henderson et al (2017). Updated geodetic modeling has redefined the deep inflation source as a shallowly dipping ~20 km × 30 km sill centered at 8 km depth (Pearse and Lundgren, 2013).…”
Section: Previous Deformation and Gas Measurementsmentioning
confidence: 99%
“…Thank you to reviewers John Pallister and David Pieri as well as associate editor Martha Savage for improving the quality of this paper. The raw data used in producing these time series are publically available through WOVOdat (http://www.wovodat.org/) data table can be found at https://doi.org/10.25921/e9h5-ke08 (the following citations are included in the supplementary information: Aiuppa et al, ; Anderson & Segall, ; Arnold et al, , ; Bagnardi, ; Bagnardi & Amelung, ; Baker, ; Barnhart & Lohman, ; Champenois et al, ; Chaussard et al, ; Delgado, ; Delgado et al, ; Delgado et al, ; Ebmeier et al, ; Ebmeier et al, , ; Ebmeier et al (); Ebmeier et al, ; Ebmeier et al, ; Feigl et al, ; Fournier et al, ; Henderson & Pritchard, ; Henderson et al, ; Holtkamp et al, ; Huppert & Woods, ; Jay, ; Jay et al, ; Jay et al, ; Lyons et al, 2014; Lau et al, ; Le Mével et al, ; Lundgren et al, , ; Lyons et al, ; McCormick et al, ; McTigue, ; Mirzaee & Amelung, ; Morales et al, 2017; Morales et al, 2016; C.G. Newhall, ; Odbert et al, ; Pinel et al, ; Pritchard et al, ; Pritchard et al, 2013; Richter et al, ; Ruch et al, ; Salzer et al, ; L. Schaefer et al, ; Schaefer et al, ; Schaefer et al, ; Stephens & Wauthier, ; Velez et al, ; Wnuk & Wauthier, ; R. Wright, ; T. J. Wright, Parsons, et al, ; Yang et al, ).…”
Section: Acknowledgmentsmentioning
confidence: 99%